CFTR Activator Increases Intestinal Fluid Secretion and Normalizes Stool Output in a Mouse Model of Constipation - Cil, Onur (Cell Mol Gastroenterol Hepatol, 2016)
BACKGROUND & AIMS: Constipation is a common clinical problem that negatively impacts quality of life and is associated with significant health care costs. Activation of the cystic fibrosis transmembrane conductance regulator (CFTR) chloride channel is the primary pathway that drives fluid secretion in the intestine, which maintains lubrication of luminal contents. We hypothesized that direct activation of CFTR would cause fluid secretion and reverse the excessive dehydration of stool found in constipation. METHODS: A cell-based, high-throughput screen was performed for 120,000 drug-like, synthetic small molecules. Active compounds were characterized for mechanism of action and one lead compound was tested in a loperamide-induced constipation model in mice. RESULTS: Several classes of novel CFTR activators were identified, one of which, the phenylquinoxalinone CFTR(act)-J027, fully activated CFTR chloride conductance with an half-maximal effective concentration (EC(50)) of approximately 200 nmol/L, without causing an increase of cytoplasmic cyclic adenosine monophosphate. Orally administered CFTR(act)-J027 normalized stool output and water content in a loperamide-induced mouse model of constipation with a 50% effective dose of approximately 0.5 mg/kg; CFTR(act)-J027 was without effect in cystic fibrosis mice lacking functional CFTR. Short-circuit current, fluid secretion, and motility measurements in mouse intestine indicated a prosecretory action of CFTR(act)-J027 without direct stimulation of intestinal motility. Oral administration of 10 mg/kg CFTR(act)-J027 showed minimal bioavailability, rapid hepatic metabolism, and blood levels less than 200 nmol/L, and without apparent toxicity after chronic administration. CONCLUSIONS: CFTR(act)-J027 or alternative small-molecule CFTR-targeted activators may be efficacious for the treatment of constipation.